2017
DOI: 10.7547/15-142
|View full text |Cite
|
Sign up to set email alerts
|

Lower-Leg and Foot Contributions to Turnout in University-Level Female Ballet Dancers

Abstract: These findings suggest that the lower leg does contribute to dancers' overall position of functional turnout. However, current methods are not useful in predicting a dancer's lower-leg contribution and alignment in functional turnout in first position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Limited hindfoot motion exposes the tibiofemoral joint to excessive external rotation. This supports our findings from earlier studies [3, 12], however the relationship only holds true to active measurements of external tibiofemoral rotation and static first position conditions. Therefore, our findings reject our hypothesis, as we solely stated passive measurements rather than passive and active measurements.…”
Section: Discussionsupporting
confidence: 92%
“…Limited hindfoot motion exposes the tibiofemoral joint to excessive external rotation. This supports our findings from earlier studies [3, 12], however the relationship only holds true to active measurements of external tibiofemoral rotation and static first position conditions. Therefore, our findings reject our hypothesis, as we solely stated passive measurements rather than passive and active measurements.…”
Section: Discussionsupporting
confidence: 92%
“…3 Two studies included dancers with ankle injury to compare their movement patterns with healthy, uninjured dancers. 77,82 Twenty-one of the 25 studies explicitly stated which genre or style their participants practiced: 12 evaluated ballet dancers, 35,37,39,41,[74][75][76][77][78]80,82,84 three evaluated jazz dancers, 11,28,29 three evaluated both ballet and contemporary dancers, 2,48,49 and tap dancers, 79 Latin ballroom, 81 and Irish dancers 7 were evaluated in one study each (Tables 5, 6, and 7). The other four studies did not specify the style of dance their participants practiced.…”
Section: Study Participantsmentioning
confidence: 99%
“…Traditional dance styles, such as classical ballet, contemporary dance, jazz, tap, ballroom Latin dance, and Irish dancing, require dancers to possess excessive joint ranges of motion (ROM) for proper technique execution and desired aesthetics. [1][2][3][4][5][6][7][8] Although these dance styles have different technical demands and style-specific movements, all styles require excessive ankle and foot ROM that may put the dancer at increased risk for injury. For example, dancers frequently transition into demipointe relevé (standing on the balls of the feet with toes extended) from plié ("to bend"; full dorsiflexion of the ankles with the knees flexed).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with these, Moller et al 42 reported ICC of 0.55 (intra-tester) and 0.50 (intertester) for measurement in a seated position. As to NHCTO, Carter et al 45 reported intra-tester ICC of 0.93 on their measurement of tibiofemoral anteversion (seated position), and Sutton-Traina et al 10 reported 0.95 for measurement of femoral version (supine position). No studies reported inter-tester reliability for NHCTO.…”
Section: Reliability Testingmentioning
confidence: 99%
“…Nine studies recorded NHCTO, including seven cross-sectional studies, [7][8][9]24,29,34,45 one cohort, 43 and one case-control study. 10 Dancers were again either prone, supine, sitting, or standing, but measurement protocols were more diverse.…”
Section: Non-hip Contributions To Turnout (Table 5)mentioning
confidence: 99%